2008
DOI: 10.1111/j.1740-8261.2008.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Magnetic Resonance Imaging for Meniscal Tears in Dogs Affected With Naturally Occuring Cranial Cruciate Ligament Rupture

Abstract: A stifle magnetic resonance (MR) imaging protocol was developed based on the appearance of the cruciate ligaments and menisci in normal dogs. Proton density images were subjectively considered to have the highest likelihood of detecting a meniscal lesion. Following this initial evaluation, the accuracy of high-field MR imaging to detect meniscal tears in dogs was evaluated in 11 dogs suffering from naturally occurring cranial cruciate ligament rupture. Dogs underwent MR imaging of the affected stifle before su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(107 citation statements)
references
References 15 publications
(31 reference statements)
9
92
2
4
Order By: Relevance
“…One study, which compared the use of 1.5 T MR with computed radiography to assess osteophytosis, subchondral bone sclerosis, joint effusion and soft tissue thickening after experimentally-induced osteoarthritis in dogs, found that MR was more sensitive than radiography for detection of the onset and progression of osteophytosis [1]. Another study found that 1.5 T MR detected meniscal tears in clinical cases of CCLR with a sensitivity of 100% and a specificity of 94% [3]. …”
Section: Introductionmentioning
confidence: 99%
“…One study, which compared the use of 1.5 T MR with computed radiography to assess osteophytosis, subchondral bone sclerosis, joint effusion and soft tissue thickening after experimentally-induced osteoarthritis in dogs, found that MR was more sensitive than radiography for detection of the onset and progression of osteophytosis [1]. Another study found that 1.5 T MR detected meniscal tears in clinical cases of CCLR with a sensitivity of 100% and a specificity of 94% [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it avoids the risk of magic angle artifact (Podadera et al 2014). Besides that, the T2-weighted FSE and PD-weighted with fat-suppressed sequences were the best to visualize joint effusion, edema and inflammation of stifle joint (Bredella et al 2000, Blond et al 2008, D'Anjou et al 2008. In another study, the diagnosis of a cranial cruciate ligament rupture, even by means of a 3T, was difficult, and was characterized by an increase in the signal intensity of a hypointense ligament (Galindo-Zamora et al 2013).…”
Section: Ligamentsmentioning
confidence: 99%
“…However, during the anatomic study of the meniscus in the low magnetic field heterogeneous signal increase in the center was observed. The authors supposed that it was due to the gradient echo sequence used and its hyperintense effect (Martig et al 2006, Blond et al 2008, Pujol et al 2011. Similarly, in a high-field study Barrett et al (2009) defined as an entire meniscus with intrameniscal increased signal intensity that did not reach meniscal margins.…”
Section: Meniscusmentioning
confidence: 99%
See 1 more Smart Citation
“…Banfield and Morrison (2000) has shown, that in order to increase accuracy of stifle imaging in MRI arthrogaphy can be done. Blond et al (2008) informed that sensitivity of MRI for meniscal tears diagnosis was 100%. Similar observation reported Bottcher et al (2010) and their results for meniscal tears were 95%.…”
Section: Knee Jointmentioning
confidence: 99%